TiO₂ band restructuring by B and P dopants - Sun, Chang Qing (2018)
An examination of the effect of B- and P-doping and codoping on the electronic structure of anatase TiO₂ by performing density functional theory calculations revealed the following: (i) B- or P-doping effects are similar to atomic undercoordination effects on local bond relaxation and core electron entrapment; (ii) the locally entrapped charge adds impurity levels within the band gap that could enhance the utilization of TiO₂ to absorb visible light and prolong the carrier lifetime; (iii) the core electron entrapment polarizes nonbonding electrons in the upper edges of the valence and conduction bands, which reduces not only the work function but also the band gap; and (iv) work function reduction enhances the reactivity of the carriers and band gap reduction promotes visible-light absorption. These observations may shed light on effective catalyst design and synthesis.